Analisis Tindak Pidana Penggelapan terhadap Rental Mobil - Bina Eradany (Departement of Mathematics Education, 2021)
The criminal act of car rental fraud resulting in the car being sold to another person. The formulation of the problem in this study is the implementation of the criminal act of selling car resale fraud to other people, the factors of the occurrence of a car rental fraud crime resulting in a car being sold to someone else and what efforts are given so that the car rental fraud crime which results in a car being sold is not widespread to society. As for the aim of the research, namely to find out the application of the criminal act of fraudulent selling of cars to other people, to find out the factors of the occurrence of criminal acts of car rental fraud resulting in cars being sold to other people and to find out the efforts given so that the crime of car rental fraud resulted in car not sold widely to the public. The results of this study indicate that the application of the criminal act of fraud, embezzlement, rental car is regulated under Articles 372, 373, 374 and 375 of the Criminal Code. Based on the several cases described in the previous section, the perpetrators of car embezzlement were charged with 4-6 years in prison. Factors causing the crime of car embezzlement include economic factors, ignorance of legal consequences, opportunities/opportunities and the weak factor of the rental party's security system. Efforts that can be made in overcoming the criminal act of embezzlement of rental cars are through preventive and repressive measures.